2021
DOI: 10.1002/lob.10433
|View full text |Cite
|
Sign up to set email alerts
|

Resources and Practices to Improve Diatom Data Quality

Abstract: Environmental programs in the UnitedStates face technical challenges that inhibit the ability to use diatoms in water quality monitoring and assessment projects. Specifically, inconsistent taxonomy can obscure diatom responses to environmental variables. Problems are the result of (1) limited access to a common set of taxonomic references, especially those that are geographically relevant, (2) inefficient enumeration protocols, (3) lack of complete and transparent documentation of taxa, and (4) limited opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This idea is supported in studies of other assemblages; Leitão et al (2016) , for example, reported that rare taxa in stream fish assemblages were generally more sensitive to anthropogenic influences than those common enough to be included in impact assessments. The use of a trait-based approach, where all the taxa are assigned to traits, could be an advantage in countries like the U.S. where around a quarter of all species in North America are still without scientific names ( Potapova and Charles, 2003 ), many of which are restricted to a particular geographical region ( Alers-García et al, 2021 ). Given that the response of diatom traits is thought to be independent of ecoregions, and, hence, trait-based indices may be transferable among ecoregions with very different diatom flora ( Soininen et al, 2016 ), our traits metrics could potentially be applied to diatoms within any ecoregion, including those undescribed taxa with restricted distributions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This idea is supported in studies of other assemblages; Leitão et al (2016) , for example, reported that rare taxa in stream fish assemblages were generally more sensitive to anthropogenic influences than those common enough to be included in impact assessments. The use of a trait-based approach, where all the taxa are assigned to traits, could be an advantage in countries like the U.S. where around a quarter of all species in North America are still without scientific names ( Potapova and Charles, 2003 ), many of which are restricted to a particular geographical region ( Alers-García et al, 2021 ). Given that the response of diatom traits is thought to be independent of ecoregions, and, hence, trait-based indices may be transferable among ecoregions with very different diatom flora ( Soininen et al, 2016 ), our traits metrics could potentially be applied to diatoms within any ecoregion, including those undescribed taxa with restricted distributions.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, whether it is necessary to use data with species-level resolution to achieve the regulatory goals for managing waters or could genus-level resolution suffice. Also, whether a species resolution is even feasible, especially when many species remain undescribed, and additional effort to document (i.e., images in voucher flora) taxa that do not fit current morphological species concepts is needed to maintain consistent taxonomy among different projects or within multi-year projects ( Alers-García et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations: (Plate 5, Figs. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The valves are 22.1-42.8 µm long and 5.4-6.5 µm wide, and stria density is 8-11 in 10 µm. The valve outline is lunate with a flat to slightly tumid ventral margin, moderately arched dorsal margin, and rounded apices.…”
Section: Red List and Rare Taxamentioning
confidence: 99%
“…In the context of a project with support from the California Lahontan Water Quality Control Board that serves to examine factors effecting nuisance algal growth in the nearshore, a diatom voucher flora was constructed to serve as the taxonomic identification resource for the west shore of Lake Tahoe. Voucher floras, as discussed by Bishop et al (2017) and Alers-García et al (2021), serve as working laboratory documents that can provide taxonomic consistency and quality control for algal enumeration during a project lifetime. They are devised as in-house taxonomic references for a specific project that provides a consistent method for analyzing large sample sets that often employ multiple analysts (Tyree et al, 2020a), and may be conducted over an extended period of years.…”
Section: Introductionmentioning
confidence: 99%